Identifying differential scheduling plans for microgrid operations under diverse uncertainties - Qiu, Haifeng (2023)
To satisfy the differential operation requirements of microgrids under the nominal and uncertain scenarios, a novel three-stage close-looped robust optimization (TSCL-RO) method is proposed to obtain more practical scheduling plans. In the first stage, the fixed startup and shutdown plans are identified considering both the cutting planes from the nominal and uncertain scenarios. According to the startup/shutdown schemes, the decision-making of the basic flexible plans under the nominal scenario is performed to minimize the operation cost in the second stage considering the second-order cone relaxed distflow model. To confront the disturbances from the power and N-k uncertainties, the basic flexible variables are revised to capture the worst-case scenario via a max-min bi-level optimization in the third stage, and the derived results are returned as feasibility cuts to preserve the robustness of the fixed plans. To solve this intractable TSCL-RO model proficiently, a tailored bi-layer chaining decomposition algorithm is further devised to handle the resulting multi-level mixed-integer second-order cone programming (MISOCP) via alternate iterations. Finally, numerical simulations verify the applicability and superiority of the investigated TSCL-RO model and the decomposition algorithm.